KEBAHAGIAAN PADA PASANGAN SUAMI ISTRI DENGAN USIA PERNIKAHAN DI ATAS 50 TAHUN - Ismatul Izzah (Jurnal Psikologi Integratif, 2019)
This study aimed to describe the happiness of couples with a marriage age above 50 years. The informants consisted of two pairs of husband and wife with a marriage age above 50 years. The method used in this research is a qualitative method with a descriptive analysis approach. Data collection techniques in this study used observation and interviews with data analysis techniques consisting of data codification, triangulation, data presentation, and conclusion. The results of the study show that married couples feel happy shown by having an attitude of gratitude and sincerity for all that is owned or through it from young to old age. The two pairs of subjects believed that in carrying out human life, God's protection was needed and there was God's intervention so that the desire to draw closer to God was stronger in the two pairs of subjects. The factors that influence the happiness of a married couple are (a) the purpose of marriage (b) commitment (c) communication (d) romanticism (e) utilization of time together with spouse (f) religion.